Community structure of artificial container-breeding flies (Insecta: Diptera) in relation to the urbanization level - Rubio, Alejandra (2012)
The changes in the community structure of flies breeding in small artificial containers along environments of different urbanization level were assessed at two spatial scales; i.e. patch and landscape. A total of 8400 water-filled flower vases were inspected in 14 cemeteries from temperate Argentina. A total of 267,013 larvae were collected in 31.1% of the inspected containers. Twenty-four species belonging to eleven Diptera families were identified. Four species (from Muscidae, Culicidae, Chironomidae, and Ceratopogonidae) represented 95.6% of the larvae collected and 93.2% of the occupied containers. For the local spatial scale, i.e. patches within cemeteries, there was no evidence that the community structure differs between open green spaces and densely built areas. For the landscape spatial scale, i.e. among cemeteries surrounded by different urbanization levels, different patterns were detected. The percentage of containers harboring larvae and the abundance (total and per container) showed a clear peak at intermediate levels of urbanization (20-40% of impervious area). The species richness and composition were similar along the gradient. Our results suggest that the urbanization level affects the studied community depending on the spatial scale.